Perancangan Sistem Informasi Manajemen Aset Berbasis Web Menggunakan Metode Scrumban (Studi Kasus: Universitas Subang) - Ardan, Tazkia Salsabila (JATISI, 2024)
Subang University is a university located in the district of Subang, West Java. With so many different faculties and locations, the asset management process at the University of Subang can no longer be carried out conventionally, especially with the increasing time, the time being added as well as the existing ones. Conventional asset management causes many problems to arise, asset optimization cannot be carried out optimally, and it is difficult to obtain evaluation materials for existing officers because there is no integrated data. This study designed an asset management information system using web technology so that it is expected to assist in the asset management process in minimizing existing problems in an integrated manner. In addition, this research will apply the Scrumban method in designing an asset management information system. To describe the design, the writer will use the unified modeling language, database design, and interface design. The result of this research is an asset management information system model which includes several aspects including system user aspects, software aspects, hardware aspects, and internet network aspects which will be implemented in the future.